Marine Biodiversity and Geographic Distributions Are Independent on Large Scales - Antell, Gwen S.; Kießling, Wolfgang; Aberhan, Martin; Saupe, Erin E. (Current Biology, 2020)
Fundamental ecological and evolutionary theories, such as community saturation and diversity-dependent diversification, assume that biotic competition restricts resource use, and thus limits realized niche breadth and geographic range size [1–3]. This principle is called competitive exclusion. The corollary (ecological release) posits that, after competitors disappear from a region, species that were previously excluded will invade. Hundreds of field experiments have demonstrated ecological release in living populations. However, few of these studies were conducted in marine environments, and almost no work extended beyond 10 years and 1,000 km2 [4, 5]. In limited investigation of marine taxa at larger spatiotemporal scales, macroecologists and paleobiologists have observed little evidence of competitive exclusion [6–9]. Here, we quantified spatial trends in the rich and densely sampled fossil history of brachiopods and bivalves, while accounting for inconsistent sampling coverage through time using a new method of spatial standardization. The number of potential competitors in a region did not explain the geographic distribution of constituent species or genera. Furthermore, although ecological release predicts species to expand after extinction events, survivors of intervals with net species loss expanded as rarely as species in other intervals. Regression model estimates indicated different spatial responses of brachiopods and bivalves, and of habitat specialists and generalists, but no effect from changes in number of potential competitors. Biotic competition may control the distribution of populations, but, on larger spatiotemporal scales, non-competitive factors may have driven biogeographic patterns of brachiopods and bivalves. Long-standing ecological and evolutionary theories assume that competition between individuals controls the cumulative resource use and geographic ranges of species. Antell et al. demonstrate that spatial distributions of marine invertebrates are incongruent with this expectation throughout the last 485 million years.
CRIS-Team Scopus Importer:2020-01-07
Keywords: bivalves; brachiopods; competition; diversity-dependent diversification; ecological release; fossil record; macroecology; niche partitioning; spatial scale; species distributions